2018
DOI: 10.1016/j.rmed.2018.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary manifestations of large, medium, and variable vessel vasculitis

Abstract: The hallmark of vasculitis is autoimmune inflammation of blood vessels and surrounding tissues, resulting in an array of constitutional symptoms and organ damage. The lung is commonly targeted in the more familiar ANCAassociated small vessel vasculitidies, but large and medium vessel vasculitides, including Takayasu arteritis, giant cell arteritis, polyarteritis nodosa, Behcet's disease, and necrotizing sarcoid granulomatosis, may also feature prominent pulmonary involvement. Pulmonary manifestations of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 113 publications
(223 reference statements)
0
16
0
Order By: Relevance
“…Aortic GCA usually remains asymptomatic during the early phase and may cause serious complications in the late phase, such as aneurysms and dissections. Differently to arteriosclerosis, aneurysms in GCA more frequently involve the thoracic aorta and seem more prone to dissection; involvement of the lungs is considered rare in this vasculitis, and may be characterized by nodules, infiltrates, lymphocytic alveolitis, alveolar hemorrhage, and unilateral pleural effusion [ 22 , 23 ]. As in TA, 18F-FDG PET is useful in the demonstration of active disease and in follow-up; however, it must be considered that the interpretation is more difficult than in TA because GCA patients are usually older and there is often concomitant arteriosclerosis [ 5 ].…”
Section: Pulmonary Vasculitismentioning
confidence: 99%
See 1 more Smart Citation
“…Aortic GCA usually remains asymptomatic during the early phase and may cause serious complications in the late phase, such as aneurysms and dissections. Differently to arteriosclerosis, aneurysms in GCA more frequently involve the thoracic aorta and seem more prone to dissection; involvement of the lungs is considered rare in this vasculitis, and may be characterized by nodules, infiltrates, lymphocytic alveolitis, alveolar hemorrhage, and unilateral pleural effusion [ 22 , 23 ]. As in TA, 18F-FDG PET is useful in the demonstration of active disease and in follow-up; however, it must be considered that the interpretation is more difficult than in TA because GCA patients are usually older and there is often concomitant arteriosclerosis [ 5 ].…”
Section: Pulmonary Vasculitismentioning
confidence: 99%
“…It typically presents with eyes involvement (uveitis), recurrent oral and genital ulcers. It may also affect other organs and systems, such as joints, the gastrointestinal system, central nervous system, cardiovascular system, and the lungs [ 23 , 24 ]. It usually presents in the second or third decade of life and the thoracic involvement is seen in 1–8% of cases.…”
Section: Pulmonary Vasculitismentioning
confidence: 99%
“…GCA-related pulmonary involvement can include pulmonary embolism, pulmonary infarction, pulmonary nodules, and pleural effusion [ 4 , 5 ]. In one study, 13% of cases had cough related to GCA and a correlation was found between inflammatory biomarkers and presence of dry cough [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…The commonest of these conditions is Kawasaki disease which, by some estimates, accounts for Pulmonary manifestations of systemic vasculitis in childhood almost half of all paediatric vasculitis. c-PAN is significantly rarer, but is notable for its ability to cause bronchial artery aneurysms that might be identified following investigation for haemoptysis, or seen incidentally in asymptomatic patients [13].…”
Section: Medium Vessel Vasculitismentioning
confidence: 99%